Utilização da análise hierárquica ponderada para o estudo dos processos erosivos lineares na bacia hidrográfica do rio Ibicuí – RS - Dias, Daniélli Flores (2021)
The present thesis has as general objective to use the weighted hierarchical analysis method to analyze the susceptibility to linear erosion processes in the hydrographic basin of the Ibicuí River. The reason for choosing the study area is due to the fact that this hydrographic basin presents intense erosive processes, mainly on the left bank of the Ibicuí River.The literature review addressed issues related to the definition and initial considerations about erosion, linear erosion processes emphasizing ravines and gullies, conditioning factors of linear erosion, in addition to geotechnologies and the use of multicriteria analysis for the study of erosion processes. The work methodology used the weighted hierarchical analysis, combined with the deductive method and was divided into three stages - cabinet stage, structuring the weighted hierarchical analysis and validation of information. As results of the research, the discussion of the conditioning factors listed for this work was presented - relief, soils, lithology and use and occupation - which were weighted and ranked to define the basin's erosive susceptibility. Subsequently, an automated crossing of the conditioning factors was carried out, which gave rise to the map of erosive susceptibility. This map was classified into five susceptibility classes - very low, low, medium, high and very high - which were validated based on the demarcation of erosive features in the study area and fieldwork carried out during the research. To validate all the information collected during the work, the susceptibility map was crossed with the map of erosive features, in order to verify and analyze if the hierarchies performed and the refined and detailed information match the distribution of the erosive processes of the study area. Thus, in the final erosive susceptibility mapping, it was observed that more than 83% of ravines and gullies occurred in areas mapped as high and very high susceptibility. This reinforces that the entire process of ranking and comparison matches all the information raised and detailed throughout the research. In conclusion, it is highlighted that the main focus of this research is that it serves to bring together the discussions for the application of territorial planning and ordering, based on the definitions of the appropriate places for the different types of use. Therefore, it is extremely important to have a detailed knowledge of the environmental dynamics, so that alternatives can be suggested that are premised on recovering or preserving the landscape in its natural and/or anthropogenic dimensions.